Characteristics of Patient with Benign Paroxysmal Positional Vertigo in Dr. Hasan Sadikin General Hospital Bandung from 2009â2013 - Kirana, Intan Datya; Dewi, Yussy Afriani; Nurhayati, Titing (Althea Medical Journal, 2016)
Background: Benign Paroxysmal Positional Vertigo (BPPV) is a vestibular disorder marked by episodesÂ of vertigo and triggered by a change in the head position. It is characterized by short yet severe episodesÂ of vertigo and possibly accompanied by nausea and vomiting. The BPPV is usually idiopathic and foundamong people aged 46â50 years old. There are pharmacological and non pharmacological treatment usedÂ for BPPV. Non-pharmacological treatment includes Epley, Semont, Lempert, Forced Prolonged Position, andBrandt-Daroff maneuvers and pharmacological onebenzodiazepine and antihistamines. This study aimed toÂ examine the characteristics of patient with BPPV based on their complaint and prescribed treatment.Methods: This was a descriptive-retrospective study conducted on AprilâJune 2014 using secondary dataÂ from medical records of patient with BPPV in Dr. Hasan Sadikin General Hospital Bandung from 2009â2013.Â The variables include gender, age, occupation, accompanying disease, complaints, supporting examinations,Â and treatment.Results: There were 74 subjects; 66.22% were female and 33.78% were male. Most of patients with BPPVÂ aged around 41â50 years old (39.19%). Furthermore, 93.24% had a major complaint of headache andÂ spinning sensation, and >60% nausea and vomiting. The most prescribed therapy was Betahistine (86.49%).Â Meanwhile, a maneuver of non-pharmacological treatment was rarely done (8.11%).Conclusions: The BPPV occurs more in older women. The major complaint is headache and spinningÂ sensation affected by the head position and accompanied by nausea and vomiting. Lastly, non-pharmacologicalÂ treatment is rarely performed in handling patient with BPPV. [AMJ.2016;3(2):275â9]DOI:Â 10.15850/amj.v3n2.800